Export Performance in Europe : What Do We Know from Supply Links? - Rahman, Jesmin; Zhao, Tianli (Washington, D.C. : International Monetary Fund, 2013)
One of the most important recent developments in international trade is the increasing interconnectedness of export production through a vertical trading chain network that streches across many countries, with each country specializing in particular stages of a good's production. Using value added trade statistics, this paper tries to dissect and reshape understanding of European exports: where exports values are created, the role of vertical supply links in export growth, what is contributing to the growth in supply links, and how comparative advantages of countries are affected by supply links over time. Our analysis finds strong role of supply links in cross-country export performance in Europe, where these links between countries grew based on physical proximity, cost differential and similarity in export structure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet